Preferences for types of inclusive family violence services among LGBTQ people in Australia - Amos, Natalie (Journal of family violence, 2024)
Purpose: LGBTQ people are less likely to seek support and face significant barriers in accessing affirmative family violence support services. Efforts to improve family violence service access must be grounded in the preferences of LGBTQ people themselves. Method: Data from a large nationwide Australian survey of the health and wellbeing of LGBTQ adults were analysed. 4,148 participants expressed a preference for family violence service provision. Multivariable logistic regressions were used to identify factors associated with preferences for family violence service provision, comparing mainstream services that are not known to be inclusive, mainstream services that are known to be LGBTQ-inclusive, and LGBTQ-specific services. Results: In total, 8.8% (n = 363) of participants indicated a preference for mainstream services, 57.5% (n = 2,383) for mainstream services that are known to be LGBTQ-inclusive and 33.8% (n = 1,402) for LGBTQ-specific services. Trans and non-binary identified people were more likely to prefer LGBTQ-specific services than cisgender participants, while bisexual, pansexual and asexual people were more likely to prefer mainstream LGBTQ-inclusive services. Participants with a regular general practitioner were more likely to prefer LGBTQ-inclusive services. Participants who had not felt supported the most recent time they reported an experience of family violence were more likely to prefer LGBTQ-specific services. Conclusion: Family violence and healthcare services require training in LGBTQ issues to provide inclusive and affirming care. The findings have implications for policy and practice in family violence care and illustrate an urgent need to reform the current narrative of family violence, which frequently excludes LGBTQ communities.